2018
DOI: 10.1007/s12540-018-0139-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ni Addition on Bainite Transformation and Properties in a 2000 MPa Grade Ultrahigh Strength Bainitic Steel

Abstract: The effects of Nickle (Ni) addition on bainitic transformation and property of ultrahigh strength bainitic steels are investigated by three austempering processes. The results indicate that Ni addition hinders the isothermal bainite transformation kinetics, and decreases the volume fraction of bainite due to the decrease of chemical driving force for nucleation and growth of bainite transformation. Moreover, the product of tensile strength and total elongation (PSE) of high carbon bainitic steels decreases wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…The morphology of ductile tearing was observed in Figure a, whereas cleavage facets existed in Figure b. It is well known that brittle fracture yields cleavage facets and leads to an inferior tensile toughness . In contrast, ductile fracture causes ductile tearing and provides a high tensile toughness.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…The morphology of ductile tearing was observed in Figure a, whereas cleavage facets existed in Figure b. It is well known that brittle fracture yields cleavage facets and leads to an inferior tensile toughness . In contrast, ductile fracture causes ductile tearing and provides a high tensile toughness.…”
Section: Resultsmentioning
confidence: 96%
“…The morphology of microstructure and tensile fracture and energy dispersive spectroscopy (EDS) analyses were conducted on a Nova 400 Nano field emission scanning electron microscope (FE‐SEM). The Image‐Pro Plus software (Media Cybernetics, Rockville, MD, USA) was utilized to measure the sizes of prior austenite grains in different specimens. In order to determine the volume fractions and carbon contents of retained austenite (RA) in different samples, the X‐ray diffraction (XRD) analysis was carried out on an Empyrean diffractometer (equipped with an unfiltered Co‐Ka radiation source) at an operating voltage of 35 kV and a current of 50 mA.…”
Section: Methodsmentioning
confidence: 99%
“…It can be observed that both the rate and the final bainite transformation amount decreased with increasing Si content when the specimens were austempered at 380 and 430 °C. Figure represents the curves of time–temperature‐transformation (TTT) for three tested steels, which were calculated by the JMatPro7.0 software . The increase of Si content makes the “ C ” curves of bainite starting transformation move to right, indicating that increasing Si content prolongs the incubation period for bainitic transformation.…”
Section: Resultsmentioning
confidence: 99%
“…It is known that brittle fracture mode leads to cleavage facet, meaning the inferior tensile toughness. Oppositely, ductile fracture results in ductile tearing, implying the high tensile toughness . The fracture surface of Si‐1 steel consisted of more amount of cleavage facets, while more amount of ductile tearing morphology appeared in the specimens of Si‐2 and Si‐3 steels.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation